Dark metabolism: a molecular insight into how the Antarctic sea-ice diatom Fragilariopsis cylindrus survives long-term darkness - Fraser Kennedy; Martin, A; John Bowman; Richard Wilson; Andrew McMinn (2019)
Light underneath Antarctic sea‐ice is below detectable limits for up to 4 months of the year. The ability of Antarctic sea‐ice diatoms to survive this prolonged darkness relies on their metabolic capability. This study is the first to examine the proteome of a prominent sea‐ice diatom in response to extended darkness, focusing on the protein‐level mechanisms of dark survival. The Antarctic diatom Fragilariopsis cylindrus was grown under continuous light or darkness for 120 d. The whole cell proteome was quantitatively analysed by nano‐LC−MS/MS to investigate metabolic changes that occur during sustained darkness and during recovery under illumination. Enzymes of metabolic pathways, particularly those involved in respiratory processes, tricarboxylic acid cycle, glycolysis, the Entner−Doudoroff pathway, the urea cycle and the mitochondrial electron transport chain became more abundant in the dark. Within the plastid, carbon fixation halted while the upper sections of the glycolysis, gluconeogenesis and pentose phosphate pathways became less active. We have discovered how F. cylindrus utilises an ancient alternative metabolic mechanism that enables its capacity for long‐term dark survival. By sustaining essential metabolic processes in the dark, F. cylindrus retains the functionality of the photosynthetic apparatus, ensuring rapid recovery upon re‐illumination.